Demystifying the Costs of Electricity Generation Technologies - Timilsina, Govinda R. (World Bank, Washington, DC, 2020)
The levelized cost of electricity is the most common indicator used to compare the cost competitiveness of electricity-generating technologies. Several studies claim that some renewable energy technologies, particularly utility-scale solar photovoltaic and onshore wind, are cost-competitive with fossil fuel–based technologies. However, there is no consensus on this point considering the wide variations in factors that influence the levelized costs of electricity across countries and technologies. This study calculates more than 4,000 levelized costs of electricity for 11 technologies, varying key input variables. The study shows that the levelized costs of electricity for renewable electricity technologies, except concentrated solar and offshore wind, are lower than those for fossil fuel–based technologies at the lower range of capital costs and discount rates of 10 percent or lower. However, for a reasonable range of input variables, calculations of the levelized costs of electricity for renewables based on reasonable parameter values do not justify the low auction prices for solar power, below US$20 per megawatt hour, recently observed in some parts of the world. The study also highlights the shortcomings of the levelized cost indicator for comparing the cost-competitiveness of different types of electricity generation technologies.